Maralixibat for the treatment of PFIC: Long‐term, IBAT inhibition in an open‐label, Phase 2 study. Issue 9 (4th May 2022) - Loomes, Kathleen M.; Squires, Robert H.; Kelly, Deirdre; Rajwal, Sanjay; Soufi, Nisreen; Lachaux, Alain; Jankowska, Irena; Mack, Cara; Setchell, Kenneth D. R.; Karthikeyan, Palaniswamy; Kennedy, Ciara; Dorenbaum, Alejandro; et al.
Abstract: Children with progressive familial intrahepatic cholestasis, including bile salt export pump (BSEP) and familial intrahepatic cholestasis–associated protein 1 (FIC1) deficiencies, suffer debilitating cholestatic pruritus that adversely affects growth and quality of life (QoL). Reliance on surgical interventions, including liver transplantation, highlights the unmet therapeutic need. INDIGO was an open‐label, Phase 2, international, long‐term study to assess the efficacy and safety of maralixibat in children with FIC1 or BSEP deficiencies. Thirty‐three patients, ranging from 12 months to 18 years of age, were enrolled. Eight had FIC1 deficiency and 25 had BSEP deficiency. Of the latter, 6 had biallelic, protein truncating mutations (t)‐BSEP, and 19 had ≥ 1 nontruncating mutation (nt)‐BSEP. Patients received maralixibat 266 μg/kg orally, once daily, from baseline to Week 72, with twice‐daily dosing permitted from Week 72. Long‐term efficacy was determined at Week 240. Serum bile acid (sBA) response (reduction in sBAs of > 75% from baseline or concentrations <102.0 μmol/L) was achieved in 7 patients with nt‐BSEP, 6 during once‐daily dosing, and 1 after switching to twice‐daily dosing. sBA responders also demonstrated marked reductions in sBAs and pruritus, and increases in height, weight, and QoL. All sBA responders remained liver transplant–free after > 5 years. No patients with FIC1 deficiency or t‐BSEP deficiency met the sBA responder criteria during the study. Maralixibat was generally well‐tolerated throughout the study. Conclusion : Response to maralixibat was dependent on progressive familial intrahepatic cholestasis subtype, and 6 of 19 patients with nt‐BSEP experienced rapid and sustained reductions in sBA levels. The 7 responders survived with native liver and experienced clinically significant reductions in pruritus and meaningful improvements in growth and QoL. Maralixibat may represent a well‐tolerated alternative to surgical intervention. Abstract : The long‐term efficacy and safety of maralixibat (a minimally absorbed, selective inhibitor of the ileal bile acid transporter) was assessed in children with BSEP or FIC1 deficiencies. Rapid and sustained reductions in sBA levels were observed in a subset of patients with non‐truncating BSEP deficiency, leading to transplant‐free survival, as well as reductions in pruritus and meaningful improvements in growth and quality of life. Maralixibat can be considered as an effective, well‐tolerated, nonsurgical alternative to surgical biliary diversion in these patients.image